Diasporas and Outsourcing : Evidence from oDesk and India - Ghani, Ejaz; Kerr, William R.; Stanton, Christopher (World Bank, Washington, DC, 2013)
This paper examines the role of the Indian diaspora in the outsourcing of work to India. The data are taken from oDesk, the world's largest online platform for outsourced contracts. Despite oDesk minimizing many of the frictions that diaspora connections have traditionally overcome, diaspora connections still matter on oDesk, with ethnic Indians substantially more likely to choose a worker in India. This higher placement is the result of a greater likelihood of choosing India for the initial contract, due in large part to taste-based preferences, and substantial path dependence in location choices. The paper further examines wage and performance outcomes of outsourcing as a function of ethnic connections.